2015
DOI: 10.1371/journal.pone.0120670
|View full text |Cite
|
Sign up to set email alerts
|

In Search of the Molecular Mechanisms Mediating the Inhibitory Effect of the GnRH Antagonist Degarelix on Human Prostate Cell Growth

Abstract: Degarelix is a gonadrotropin-releasing hormone (GnRH) receptor (GnRHR) antagonist used in patients with prostate cancer who need androgen deprivation therapy. GnRHRs have been found in extra-pituitary tissues, including prostate, which may be affected by the GnRH and GnRH analogues used in therapy. The direct effect of degarelix on human prostate cell growth was evaluated. Normal prostate myofibroblast WPMY-1 and epithelial WPE1-NA22 cells, benign prostatic hyperplasia (BPH)-1 cells, androgen-independent PC-3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 61 publications
3
21
0
Order By: Relevance
“…Thus, results that were observed for primary BPH cells in this study seem to be specific for the antagonist degarelix. In agreement with recent studies showing a direct inhibitory effect of degarelix on human prostate cell lines growth attributed to increased apoptosis [48], the inhibitory effects of degarelix on primary BPH cell growth is likely mediated by increased caspase 3/7 levels inducing apoptosis.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Thus, results that were observed for primary BPH cells in this study seem to be specific for the antagonist degarelix. In agreement with recent studies showing a direct inhibitory effect of degarelix on human prostate cell lines growth attributed to increased apoptosis [48], the inhibitory effects of degarelix on primary BPH cell growth is likely mediated by increased caspase 3/7 levels inducing apoptosis.…”
supporting
confidence: 91%
“…We recently reported that degarelix exerts a direct effect on human prostate cell lines including normal prostate myofibroblast WPMY-1 and epithelial WPE1-NA22 cells, benign prostatic hyperplasia (BPH)-1 cells, androgen-dependent LNCaP prostate cancer cells, and VCaP cells derived from a patient with castration-resistant prostate cancer [48]. The results obtained with the primary BPH cells point to the same general observation with respect to the biological response to degarelix: the inhibition of cell growth.…”
mentioning
confidence: 99%
“…Additionally, we further assessed impact of NQO1 absence on prostatic hyperplasia in other types of prostate‐related cell lines. Previously, Sakai, Martinez‐Arguelles, Patterson, Chaurand, and Papadopoulos () reported different hormone‐related gene expressions in different type of established prostate cell lines (Sakai et al., ). This was in lined with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It is only known that leukotriene B4 receptor antagonist can cause inhibition of the ovulation in rats [13], that the administration of leukotriene D4 antagonists' results in lack of progression to the luteal phase of the estrous cycle [14] and that corpus luteum produced leukotriene B4 inversely correlated with the secretion rates of progesterone [7]. Furthermore, GnRH antagonist may act on various pathways by inhibiting MAPK [15] or by inducing apoptosis [16] and nitric oxide synthesis [17], explaining potential effects on OHSS. Finally, Heparin, which controls the risk of thrombosis, blastocyst apposition, adherence and implantation as well as trophoblast differentiation and invasion [18], caused a slight reduction in the vascular permeability in our experiments.…”
Section: Discussionmentioning
confidence: 99%